Audit failure of New Zealand finance companies – An exploratory investigation. Issue 3 (1st August 2016) - Kabir, Humayun; Su, Li; Rahman, Asheq
Abstract : Purpose: The setting of private finance companies that failed in New Zealand during 2006-12 was characterized by weaker corporate governance and enforcement of securities law. This paper explores audit failure in this setting and examines whether auditors erred in their audits of the failed finance companies and whether the audit failure rate of Big N auditors was different from that of non-Big N auditors. Design/methodology/approach: This paper adopts the archival research method, and utilizes three sets of evidence to assess audit failure – the frequency of going concern opinion (GCO) prior to failure, misstatements in the last audited financial statements, and the violation of the Code of Ethics. Findings: The study finds that only 41% of the sample companies received the GCO in their last audit prior to failure, and provides evidence of material misstatements in the financial statements of a number of failed finance companies that received clean audit opinions prior to failure and breaches of the Code of Ethics by a number of auditors. These results strongly indicate audit failure for a number of failed finance companies. The audit failure rate, however, appears less for Big N auditors than for non-Big N auditors. Practical implications: The study draws attention of the stock market regulator and the accounting profession to an area, the audit of private finance companies, that needs better quality audits. Originality/value: This paper provides systematic evidence of audit failure in failed finance companies in New Zealand. It also furnishes preliminary evidence of Big N auditors compensating for weaker corporate governance.